BIOCHEMICAL COMPONENTS IN ANTERIOR ADDUCTOR MUSCLES IN FRESHWATER BIVALVE MOLLUSCS, Lamellidens corrianus. (International Journal of Food and Nutritional Sciences, 2022)
Bivalves mollouscs are very diverse animals which make a major contribution and had asignificant role to play in freshwater ecosystem. Biochemical composition in Lamelliden corrianus ,the freshwater species collected from Nanadrabad Pond near Khultabad, Aurangabad District,varied seasonally . An inversely correlation with the protein and lipid constituents was observedduring the summer and winter season. The fluctuation in biochemical content might be due to theimpact on the endogenous and exogenous factors and the triggering role of cerebral ganglionablation.